Joe Joe - Serfozo, Mary (Margaret K. McElderry Books ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1993)
During an active outing, Joe Joe produces such sounds as "Bang bang," "Clap clap," and "Splash splash."